Pengrajin Emas di Kabupaten Soppeng - Mr. Azwan; Mr. Jumadi (Rayhan Intermedia, 2022)
This study aims to determine: (1) The work ethic of gold craftsmen in the process of making jewelry in Watu Toa Village., (2) Socio-economic life and the level of welfare of gold craftsmen in Watu Toa Village. The research used a qualitative research type with an ethnographic approach and a multidisciplinary theoretical approach by applying the concepts of other social sciences such as economics and cultural anthropology. Then analyzed and written descriptively. So that the author can describe in depth and thoroughly the gold craftsmen in Watu Toa Village. The data collection technique is done by using the method of observation, interviews, documentation. Based on the results of the study, (1) Judging from their work ethic, most goldsmiths have the spirit of hard work, are conscientious, honest, and have responsibility and future orientation, so the researcher describes the work ethic of the Bugis people as the way of life of the Bugis people in working until achieve success in this world and the hereafter. The Bugis work ethic includes Reso (hard work), Getteng (steadfastness), Lempu (honesty), Appasitinajang (decency), and Siri' (self-respect). (2) Socio-economic life and welfare level of gold craftsmen in Watu Toa Village. The social development of the gold craftsman's life is seen from year to year continuing to increase, this is because the demand for ring orders on the market continues to advance, so that work as a gold craftsman is able to meet the economic needs of the family, while the level of welfare of gold craftsmen there are two, namely in terms of material and spiritual.